Tanggapan Etis Kristen Terhadap Pengaruh Budaya Digital di Kalangan Mahasiswa - Blegur, Romelus; Sinaga, Rajokiaman; Susanto, Sulianus (Jurnal Teologi Kontekstual Indonesia, 2023)
Digital culture seems to be well received in society because the benefits are unavoidable. This should be acknowledged, but this welcome should also be anticipated with a critical attitude because in contrast to its usefulness, digital technology also contributes to the emergence of negative influences and impacts on its users. This is also a concern for STT ATI students because digital culture has also permeated their life context. In this regard, the purpose of this study is to examine the experiences of STT ATI students amid digital flow to see these problems. This study uses a qualitative research method with a phenomenological study. The results of this study are that: first, STT ATI students quite understand digital culture based on their experience; second, digital culture has an impact on them, both positively and negatively; third, ethically they have a fairly good response in dealing with digital challenges, but on the other hand there are also weaknesses in perceptions about the subject. In this regard, more intense training is needed so that they are ready to face the digital era with all its consequences.